Pengoptimalan Pelayanan pada Stasiun Pengisian Bahan Bakar Umum (SPBU) Menggunakan Model Antrian Multiple Channel Single Phase - Manik, Rischi Sugiarti; Sirait, Debora Exaudi; Sianturi, Rektor (Bulletin of Community Engagement, 2024)
Queues are a phenomenon that often occurs in people's lives, especially in the service industry, such as what happens at SPBU 14.211.207 Pematangsiantar where queues start in the morning. This research aims to determine the optimal level of service system for refueling at SPBU 14.211.07 Pematangsiantar. The type of research used in this research is applied research, namely research carried out to obtain information used to solve problems using quantitative methods to determine the optimal level of service systems at gas stations. Data collection was carried out by observing and recording queues that occurred in the morning. The queuing model used is Multiple Channel Single Phase with First In First Out (FIFO) queuing discipline. From the results of calculating the performance of the queuing system at SPBU 14.211.207 Pematangsiantar, adding or more servers will reduce the service busyness level (p), where when using one server the busyness level is 80%, whereas when using two servers the busyness level is 40%. Keywords: Service Optimization, Multiple Channel Queuing Model, Multiple Channel Single Phase